Heat Transfer at Couette Flow with Due Account of Friction Heat - V. A. Kudinov; I. V. Kudinov (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2011)
An approximate analytical solution of a non-linear problem concerning heat transfer in the liquid at Couette flow with due account of friction heat has been obtained on the basis of the Kantarovich orthogonal method. The solution has made it possible to carry out temperature investigations at small values of an axial coordinate. Being obtained in the fifth approximation the solution has permitted for the first time to value liquid temperature within the range of the axial spatial coordinate. The analysis of the obtained results has revealed that a temperature maximum shift to motionless flow has been observed at small values of the axial coordinate.It is possible to make a conclusion that in order to protect devices that are moving with high speed in various media it is necessary to organize boundary layer disruption that allows to avoid stabilization of a temperature field in a flow which promotes wall over-heating due to energy dissipation.